Antimicrobial Resistance: A Dentists’ Prospective - K. Swapna Kumari1 , Patitpaban Dash2 , E. Subudhi3 , Satabdi Pattnaik4 , Naomi Ranjan Singh3 , Debka (Institute of Medico-legal Publications Pvt Ltd, 2020)
Antimicrobial resistance has turned from prediction to reality in a few decades and exerts a significantburden globally with a loss of approximately seventy thousand lives each year. Dentistry accounts forapproximately three to eleven percent of all antibiotic prescriptions worldwide. The human oral cavity is ahuge reservoir of more than 750 microbial species. Oral microbial biofilm formation such as dental plaquethat initiates periodontal diseases and dental caries is the major reason for the antimicrobial therapy failureand rise in resistance against the action of antimicrobials. Biofilm bacteria embedded with a matrix ofextracellular polysaccharides are more than 10,000 times less sensitive to antimicrobials than free-floatingplanktonic bacteria. A thorough understanding of the mechanism will provide an effective solution tocombat the current problem such as developing novel antimicrobials, method that enhance the effectivenessof antibiotics by modifying the antibiotic structure or disrupting biofilm, or altering the outer membranestructure of bacterial cell walls to neutralize the resistant enzymes. Use of novel strategies e.g. nano-drugdelivery system to facilitate drug entry into the cell; liposome for efficient local delivery of drug of choicein the treatment of caries, periodontitis and also for anesthetic purposes. This paper provides a review of theliterature based on the studies on oral biofilm, its formation, and importance in drug resistance, mechanismof drug action and development of its drug resistance and various measures to combat it and the scope ofdentists in limiting the progression of antibiotic resistance.